2017
DOI: 10.3892/ijo.2017.4123
|View full text |Cite
|
Sign up to set email alerts
|

Human amniotic epithelial cells inhibit growth of epithelial ovarian cancer cells via TGF-β1-mediated cell cycle arrest

Abstract: It is reported that human amniotic epithelial cells (hAECs) endow intrinsic antitumor effects on certain kinds of cancer. This research was designed to evaluate whether hAECs endowed potential anticancer properties on epithelial ovarian cancer (EOC) cells in vivo and in vitro, which has not been reported before. In this study, we established a xenografted BALB/c nude mouse model by subcutaneously co-injecting ovarian cancer cell line, SK-OV-3, and hAECs for 28 days. In ex vivo experiments, CCK-8 cell viability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 35 publications
0
35
0
Order By: Relevance
“…Whether or not hAMSC, skin-derived human fibroblasts and, partially, Saos-2 cells adopt the same mechanism of inhibition of T24 cell proliferation needs to be addressed. Concerning the possible mechanism used by hAM-derived cells, Magatti et al (2012) showed that hAMSC induce cell cycle arrest in hematopoietic and non-hematopoietic cancer cells ( Magatti et al, 2012 ) and Bu et al (2017) demonstrated that hAEC induce cell cycle arrest in epithelial ovarian cancer cells ( Bu et al, 2017 ). In detail, Magatti et al demonstrated that the cell cycle arrest is induced by down-regulation in the expression of positive regulators of the cell cycle (cyclins D2, E1, H; cyclin-dependent kinases-2, -4, -6; mini-chromosome maintenance complex, proliferating cell nuclear antigen) and upregulation of the cell cycle inhibitors (G2 cyclin, CDK inhibitor 1A, CDK inhibitor N2B).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Whether or not hAMSC, skin-derived human fibroblasts and, partially, Saos-2 cells adopt the same mechanism of inhibition of T24 cell proliferation needs to be addressed. Concerning the possible mechanism used by hAM-derived cells, Magatti et al (2012) showed that hAMSC induce cell cycle arrest in hematopoietic and non-hematopoietic cancer cells ( Magatti et al, 2012 ) and Bu et al (2017) demonstrated that hAEC induce cell cycle arrest in epithelial ovarian cancer cells ( Bu et al, 2017 ). In detail, Magatti et al demonstrated that the cell cycle arrest is induced by down-regulation in the expression of positive regulators of the cell cycle (cyclins D2, E1, H; cyclin-dependent kinases-2, -4, -6; mini-chromosome maintenance complex, proliferating cell nuclear antigen) and upregulation of the cell cycle inhibitors (G2 cyclin, CDK inhibitor 1A, CDK inhibitor N2B).…”
Section: Discussionmentioning
confidence: 99%
“…Altogether, hAMSC resulted in cycle arrest of cancer cells in the G 0 /G 1 phase and prevention of cell cycle progression to S phase (Magatti et al, 2012). Similarly, Bu et al showed that there was an increase in expression of negative regulators of cell cycle progression, namely p16INK4A and p21 and also demonstrated that TGF-β1 secreted from hAEC plays an important role in cell cycle arrest (Bu et al, 2017). Additionally, Niknejad et al have also shown that cell cycle inhibition can be also caused by inhibition of the heat shock protein 90 (HSP90) (Niknejad et al, 2013b).…”
Section: Ham-derived Cells Reduce the Proliferation Of Muscle-invasivmentioning
confidence: 90%
See 1 more Smart Citation
“…Mechanistically, the expression of telomerase hTERT in hAESCs is not detected, explaining why hAESCs do not generate tumors. Notably, several studies demonstrated that hAESCs could inhibit tumor cell growth and induce apoptosis of cancer cells, including HeLa cells and breast and ovarian cancer cells [ 94 , 95 , 96 ]. However, Yang et al reported that co-injection of hAESCs and Raji tumor cells into immunodeficient mice shows a similar survival duration when compared with the mice receiving only Raji cells, which indicated hAESCs have little effect on tumor growth [ 29 ].…”
Section: The Safety Evaluation Of Human Amniotic Epithelial Stem Cmentioning
confidence: 99%
“…Several studies have indicated that HAM might display anticancer activity. A suppression of different cancer lines by the addition of HAM in vitro has been shown, but clinical studies are missing [42,43]. In the presented protocol oncologic results are being recorded to assess the biochemical recurrence.…”
Section: Discussionmentioning
confidence: 99%